The Influence of Marketing Mix and Service Quality on Consumer Satisfaction at the Palugada Nita Rap Bouquet Shop - Debiana, Nita; Siregar, Zulkifli Musannip Efendi; Harahap, Aziddin (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The purpose of this research is to determine the influence of the marketing mix and service quality on consumer satisfaction at the Palugada Nita Rap Bouquet Shop with service quality as an intervening variable. Data processing techniques use SPSS data analysis. The population in this study were consumers at the Palugada Nita RapLabuhanbatu Bouquet Shop. The sample collection technique used was probability sampling which aimed at random sampling incidents, the number of samples used was 100 consumers at the Palugada Nita Rap Bouquet Shop. Researchers conclude that the Marketing Mix through Service Quality has a significant impact on Consumer Satisfaction in terms of the Sig value (0.000) which is less than 0.05. In the t-test, it is known that the Sig value is smaller than 0.05 and the calculated t value is greater than the t table (1.984), so it is concluded that the marketing mix and service quality have an independent (partial) impact on consumer satisfaction and it is concluded that the marketing mix and quality have a simultaneous impact on consumer satisfaction. based on the f test where the Sig value is smaller than 0.05 and the calculated f is greater than the f table (3.09). It is known that the direct impact that the Marketing Mix has on Consumer Satisfaction is 0.427 and the indirect impact is 0.289, so it can be concluded that the direct impact is 0.427 > from the indirect impact value of 0.289 and based on the R-Square of 0.916, the contribution value of the marketing mix through quality service to customer satisfaction, namely 91.6%.